Strategic thinking for cyber resilience from the perspectives of Malaysian public sector - Talib, Shuhaili; Jeong, Jongkil Jay; Maynard, Sean; Abdul Molok, Nurul Nuha; Ahmad, Atif (IEEE Xplore, 2024)
As the reliance on digitalization and interconnected environment is on the rise, the need to think strategically in order to withstand sophisticated cyber-attacks is vital. Nevertheless, the role of strategic thinking in cyber resilience is limited especially in the public sector organizations. Hence, this paper proposes that through strategic thinking, improvement in cybersecurity knowledge, behavior and institutional capacity can be achieved to make the public sector organizations be more prepared in facing cyber-attacks. Through qualitative research approach employing interviews as the primary data collection method and thematic analysis for data analysis, this study highlights the importance of strategic thinking to improve the cyber resilience of Malaysia’s critical infrastructure against cyber-attacks. From the review of literature, elements of strategic thinking have been identified. Amongst these elements, findings suggest that system, ethical, visionary and intuitive thinking play critical roles in decision-making process which leads to the development and implementation of cybersecurity strategies, policies and law in the Malaysian public sector organizations.